Easily adhesive film
A copolymerized polyester resin layer on a semi-aromatic polyamide resin base film addresses the adhesion issue with metal plates, ensuring strong bonding and durability in transparent flexible printed circuit boards, especially for LED screens.
Patent Information
- Application Number
- JP2023094446
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-08
- Publication Date
- 2024-12-19
AI Technical Summary
Existing easily adhesive films for transparent flexible printed circuit boards, particularly those using semi-aromatic polyamide resin, fail to provide sufficient adhesion with metal plates, leading to peeling during processes like etching and reflow.
A copolymerized polyester resin-based easy-adhesive layer is applied to a semi-aromatic polyamide resin base film, enhancing adhesion with metal plates by ensuring a peel strength of 8.0 N/15mm or more, while maintaining transparency and heat resistance.
The film achieves high adhesive strength with metal plates, suitable for use in transparent flexible printed circuit boards, particularly in LED screens, with improved durability through processes like soldering and reflow.
Smart Images

Figure 2024176150000001 
Figure 2024176150000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an easily adhesive film having an easily adhesive layer on at least one surface of a base film. [Background technology]
[0002] With the widespread use of LED displays in recent years, transparent LED screens are being developed. Transparent LED screens can transmit text and image information, and can also utilize aesthetic shapes, patterns, colors, and other designs behind the screen. Flexible printed circuit boards that are flexible and transparent are required for the development of transparent LED screens. The substrate film that constitutes a transparent flexible printed circuit board is required to have visibility that allows the user to see through to the other side without any problems, as well as adhesion to metals such as copper foil and metal oxides that form the circuit. In addition, the substrate film is required to have heat resistance and thermal dimensional stability that do not deteriorate during the heat pressing process, in which the copper foil and bonding sheet are bonded by heating to 150°C or more, and the reflow process for soldering at 200°C or more. Films made from semi-aromatic polyamide resins, which are polycondensates of aliphatic diamines and terephthalic acid, are superior in various performance aspects, including heat resistance, compared to aliphatic polyamide films, and are used in a variety of electronic devices and optical components.
[0003] For example, Patent Document 1 discloses that an easy-adhesion film in which an easy-adhesion layer made of a urethane resin is formed on a substrate film of a semi-aromatic polyamide resin has excellent optical properties and adhesion to the substrate film. Patent Document 2 discloses that a laminate in which a metal plate is laminated on a substrate film of a semi-aromatic polyamide resin via an adhesive layer made of a dimer acid polyamide resin has adhesion durability against a wide range of temperature changes. However, although the adhesive film disclosed in Patent Document 1 has excellent adhesion to the base film, there is no mention of adhesion to the metal plate. In addition, the laminate disclosed in Patent Document 2 has low adhesive strength to the metal plate, so that the metal plate may peel off during the etching process or reflow process of the metal plate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2021-47295 [Patent Document 2] International Publication No. 2019 / 054426 Summary of the Invention [Problem to be solved by the invention]
[0005] An object of the present invention is to provide an easily adhesive film that enables lamination of a substrate film made of a semi-aromatic polyamide resin and a metal plate with high adhesive strength. [Means for solving the problem]
[0006] As a result of extensive research to solve the above-mentioned problems, the inventors discovered that an easy-adhesion layer containing a copolymerized polyester resin formed on at least one side of a substrate film made of a semi-aromatic polyamide resin has excellent adhesion to a metal plate and can solve the above-mentioned problems, thereby arriving at the present invention.
[0007] That is, the gist of the present invention is as follows. (1) An easy-adhesion film having an easy-adhesion layer on at least one surface of a base film, The base film is made of a semi-aromatic polyamide resin, The easy-adhesion layer contains a copolymer polyester resin, An easily adhesive film, characterized in that in a laminate in which a metal plate is laminated on the surface of an easily adhesive layer, the peel strength between the base film and the metal plate is 8.0 N / 15 mm or more. (2) The easily adhesive film according to (1), wherein the easily adhesive layer is formed using a resin composition containing 100 parts by mass of a copolymerized polyester resin, 3 to 13 parts by mass of an epoxy compound, and 0.3 to 0.9 parts by mass of an imidazole compound. (3) The copolymer polyester resin is The acid component contains 30 mol % or more of isophthalic acid, The easily adhesive film according to (1) or (2), characterized in that the glycol component contains 30 mol % or more of a glycol having a side chain and 1 to 20 mol % of a polyalkylene glycol having a repeating unit with 2 to 4 carbon atoms and a number average molecular weight of 200 or more. (4) The easily adhesive film according to (1) or (2), wherein the copolymer polyester has an acid value of 2 to 8 mgKOH / g and a glass transition temperature of -10 to 10°C. (5) The easily adhesive film according to (1) or (2), characterized in that the base film retains 80% or more of a tensile strength and 80% or more of a tensile elongation after heat treatment at 180°C for 30 minutes. (6) A laminate in which a metal plate is laminated on the adhesive layer surface of the adhesive film described in (1) above. (7) The laminate according to (6), characterized in that the peel strength between the substrate film and the metal plate is 8.0 N / 15 mm or more. (8) The laminate according to (6) or (7), wherein the metal sheet is a copper foil. (9) An optical component using the laminate according to (6) or (7) above. Effect of the Invention
[0008] The adhesive film of the present invention has excellent transparency and heat resistance, and can be laminated with a metal plate with high adhesive strength. Therefore, the adhesive film of the present invention can be suitably used for transparent flexible printed circuit boards such as LED screens. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The present invention will be described in detail below. The easy-adhesion film of the present invention has an easy-adhesion layer on at least one surface of a base film, the base film being made of a semi-aromatic polyamide resin, and the easy-adhesion layer containing a copolymer polyester resin.
[0010] <Base film> The substrate film constituting the easy-adhesion film of the present invention is made of a semi-aromatic polyamide resin, which has an excellent balance of mechanical properties such as heat resistance and flex resistance. In the present invention, the semi-aromatic polyamide resin is composed of a dicarboxylic acid component and a diamine component, and has an aromatic component in the dicarboxylic acid component or the diamine component.
[0011] The dicarboxylic acid component constituting the semi-aromatic polyamide resin is preferably mainly composed of terephthalic acid, and examples of the dicarboxylic acid component other than terephthalic acid include aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, and octadecanedioic acid, and aromatic dicarboxylic acids such as 1,4-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,2-naphthalenedicarboxylic acid, and isophthalic acid. The proportion of terephthalic acid in the dicarboxylic acid component is preferably 60 to 100 mol %.
[0012] The diamine component constituting the semi-aromatic polyamide resin is preferably mainly composed of an aliphatic diamine having 4 to 15 carbon atoms. Examples of the aliphatic diamine having 4 to 15 carbon atoms include 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,14-tetradecanediamine, and 1,15-pentadecanediamine. These may be used alone or in combination of two or more.
[0013] The semi-aromatic polyamide resin is preferably a semi-aromatic polyamide resin consisting of a dicarboxylic acid component consisting only of terephthalic acid (100 mol % terephthalic acid) and a diamine component containing 1,9-nonanediamine and 2-methyl-1,8-octanediamine at a total content of 100 mol % in the diamine component, or a semi-aromatic polyamide resin consisting of a dicarboxylic acid component consisting only of terephthalic acid (100 mol % terephthalic acid) and a diamine component containing 1,10-decanediamine.
[0014] The semi-aromatic polyamide resin may be copolymerized with lactams such as ε-caprolactam, ζ-enantholactam, η-capryllactam, ω-laurolactam, etc., within the scope of the present invention.
[0015] The type and copolymerization ratio of the monomers constituting the semi-aromatic polyamide resin are preferably selected so that the melting point (Tm) of the resulting semi-aromatic polyamide resin is in the range of 270 to 350° C. If the Tm of the semi-aromatic polyamide resin is less than 270° C., the heat resistance of the resulting film may be insufficient. On the other hand, if the Tm of the semi-aromatic polyamide resin exceeds 350° C., thermal decomposition may occur during film production.
[0016] The semi-aromatic polyamide resin may contain a polymerization catalyst and an end-capping agent. Examples of the end-capping agent include acetic acid, lauric acid, benzoic acid, octylamine, cyclohexylamine, and aniline. Examples of the polymerization catalyst include phosphoric acid, phosphorous acid, hypophosphorous acid, and salts thereof.
[0017] As the semi-aromatic polyamide resin, commercially available products can be suitably used, such as "Genesta (registered trademark)" manufactured by Kuraray Co., Ltd., "Zecot (registered trademark)" manufactured by Unitika Ltd., "Reny (registered trademark)" manufactured by Mitsubishi Engineering Plastics Corporation, "Arlen (registered trademark)" manufactured by Mitsui Chemicals, Inc., "Ultramid (registered trademark)" manufactured by BASF, and Nylon MXD6 manufactured by Mitsubishi Gas Chemical Company, Inc.
[0018] Semi-aromatic polyamide resins can be produced by methods known as methods for producing crystalline polyamides. For example, there are solution polymerization or interfacial polymerization methods (Method A) using acid chloride and diamine components as raw materials, a method (Method B) of producing a low polymer using dicarboxylic acid components and diamine components as raw materials and polymerizing the low polymer by melt polymerization or solid-phase polymerization, a method (Method C) of producing a salt and a crushed mixture of low polymer using dicarboxylic acid components and diamine components as raw materials and polymerizing the mixture in a solid phase, and a method (Method D) of producing a salt using dicarboxylic acid components and diamine components as raw materials and polymerizing the salt in a solid phase.
[0019] In the B method, for example, a nylon salt prepared by mixing a diamine component, a dicarboxylic acid component, and a polymerization catalyst all at once is heated and polymerized at a temperature of 200 to 250°C to obtain a low polymer. The intrinsic viscosity of the low polymer is preferably 0.1 to 0.6 dL / g. By setting the intrinsic viscosity of the low polymer in this range, there is an advantage that the polymerization rate can be increased without causing a collapse of the molar balance of the carboxyl group in the dicarboxylic acid component and the amino group in the diamine component in the subsequent solid-phase polymerization or melt polymerization. If the intrinsic viscosity of the low polymer is less than 0.1 dL / g, the polymerization time may be long, resulting in poor productivity. On the other hand, if it exceeds 0.6 dL / g, the obtained semi-aromatic polyamide resin may be colored. The solid-state polymerization of the low polymer is preferably carried out under reduced pressure or in an inert gas flow. The temperature of the solid-state polymerization is preferably 200 to 280°C. By setting the temperature of the solid-state polymerization within this range, coloration and gelation of the obtained semi-aromatic polyamide resin can be suppressed. If the temperature of the solid-state polymerization is less than 200°C, the polymerization time becomes long, and the productivity may be poor. On the other hand, if the temperature exceeds 280°C, coloration and gelation may occur in the obtained semi-aromatic polyamide resin. The melt polymerization of the oligomer is preferably carried out at a temperature of 350° C. or less. If the polymerization temperature exceeds 350° C., decomposition or thermal deterioration of the semi-aromatic polyamide resin may be accelerated. Therefore, a film obtained from such a semi-aromatic polyamide resin may have poor strength and appearance. The above melt polymerization also includes melt polymerization using a melt extruder.
[0020] In the C method, for example, a suspension of molten aliphatic diamine and solid aromatic dicarboxylic acid is stirred and mixed to obtain a mixed liquid. Then, in this mixed liquid, a reaction of aromatic dicarboxylic acid and aliphatic diamine to produce a salt and a reaction of the produced salt to produce a low polymer are carried out at a temperature lower than the melting point of the semi-aromatic polyamide resin to be finally produced, to obtain a mixture of salt and low polymer. In this case, crushing may be carried out while the reaction is carried out, or the reaction may be taken out once after the reaction and then crushed. Then, the obtained reaction product is solid-phase polymerized at a temperature lower than the melting point of the semi-aromatic polyamide resin to be finally produced, and the molecular weight is increased to a predetermined molecular weight, to obtain a semi-aromatic polyamide resin. The solid-phase polymerization is preferably carried out in an inert gas stream such as nitrogen at a polymerization temperature of 180 to 270°C and a reaction time of 0.5 to 10 hours.
[0021] In the D method, for example, aromatic dicarboxylic acid powder is heated in advance to a temperature equal to or higher than the melting point of the aliphatic diamine and equal to or lower than the melting point of the aromatic dicarboxylic acid, and an aliphatic diamine is added to the aromatic dicarboxylic acid powder at this temperature without substantially containing water so as to maintain the state of the aromatic dicarboxylic acid powder, thereby preparing a salt. The obtained salt is then solid-phase polymerized at a temperature lower than the melting point of the semi-aromatic polyamide resin to be finally produced, and the molecular weight is increased to a predetermined molecular weight, thereby obtaining a semi-aromatic polyamide resin. The solid-phase polymerization is preferably carried out in an inert gas stream such as nitrogen, at a polymerization temperature of 180 to 270°C and a reaction time of 0.5 to 10 hours.
[0022] The substrate film is composed of the above-mentioned resin, but may contain known additives such as, for example, antioxidants, stabilizers, UV absorbers, pigments, dyes, antistatic agents, plasticizers, antioxidants, organic or inorganic particles, fillers, and crosslinking agents, provided that the effects of the present invention are not impaired.
[0023] Various methods can be used to incorporate the additives into the semi-aromatic polyamide film, representative of which are as follows: (A) Method of adding during polymerization of semi-aromatic polyamide resin (B) Masterbatch method in which the compound is added directly to semi-aromatic polyamide resin and melt-kneaded to prepare pellets (C) Direct addition to semi-aromatic polyamide resin during film production and melt-kneading in an extruder (D) Direct addition to the extruder during film production and melt kneading
[0024] In the present invention, the surface of the semi-aromatic polyamide film may be subjected to various surface treatments such as corona treatment, anchor coating treatment, plasma treatment, acid treatment and flame treatment, if necessary.
[0025] <Physical properties of semi-aromatic polyamide film> In the present invention, the semi-aromatic polyamide film preferably retains 80% or more, and more preferably 90% or more, of the tensile strength and tensile elongation measured in the longitudinal and transverse directions, respectively, after heat treatment at 180° C. for 30 minutes according to JIS K 7127. Films with retention rates below 80% may break during processing.
[0026] The thickness of the semi-aromatic polyamide film is more preferably 10 to 150 μm, and more preferably 20 to 100 μm. If the thickness of the semi-aromatic polyamide film exceeds 150 μm, the transparency is impaired, and if it is less than 10 μm, the mechanical strength is poor. In particular, for transparent LED screen applications, the semi-aromatic polyamide film is preferably 50 to 100 μm in thickness, and if it is less than 50 μm in thickness, it is prone to bending, making it difficult to mount an LED unit, etc.
[0027] <Method of manufacturing semi-aromatic polyamide film> Next, an example of a method for producing a semi-aromatic polyamide film will be described. The method for producing a semi-aromatic polyamide film includes the steps of: (a) A step of forming an unstretched film made of a semi-aromatic polyamide resin (b) Stretching the film (c) A step of heat-setting the stretched film at 250°C (Tm-5°C) (d) Winding the stretched film It is preferred that the compound contains
[0028] First, an example of the above step (a) will be described. The semi-aromatic polyamide resin used as the raw material for the semi-aromatic polyamide film may be a mixture of virgin raw materials, or may be a mixture of non-standard films or scraps generated as edge trimmings during the production of the semi-aromatic polyamide film, or may be a mixture of the scrap mixture and virgin raw materials. These mixtures may be performed by known methods such as a dry blending method using a known device or a kneading method in which the materials are melt-kneaded and mixed using a single-screw or twin-screw extruder.
[0029] A sufficiently dried semi-aromatic polyamide resin is fed to an extruder, melted at a temperature at which it is sufficiently plasticized and exhibits fluidity, passed through a filter selected as necessary, and extruded into a sheet through a T-die. The extruded sheet is then brought into close contact with a cooling drum adjusted to 20 to 40°C, rapidly cooled and solidified, to obtain an unstretched film. The obtained unstretched film usually has a thickness of about 30 μm to 3 mm and has excellent properties as it is, but it is preferable to biaxially stretch it in order to improve properties such as mechanical properties. The method for obtaining an unstretched film by bringing the molten resin into contact with a moving cooling body and then cooling and solidifying it is not particularly limited, but methods such as air knife casting, static electricity application, and vacuum chamber methods can be used. The above method can produce a single-layer film consisting of one layer, but a film having a multilayer structure can be produced by the above method in which the semi-aromatic polyamide resins constituting each layer are melted and extruded separately, laminated and fused before solidification, and then biaxially stretched and heat-set, or by melting and extruding two or more layers separately to form a film, and then laminated and fused together in an unstretched state or after stretching. From the viewpoint of process simplicity, it is preferable to use a multilayer die and laminate and fused together before solidification.
[0030] Next, an example of the above step (b) will be described. The resulting unstretched film is uniaxially oriented by a uniaxial stretching method, or biaxially oriented by a biaxial stretching method. As the biaxial stretching method, flat-type sequential biaxial stretching method, flat-type simultaneous biaxial stretching method, tubular method, etc. can be used. Among them, flat-type simultaneous biaxial stretching method is most suitable because it has good film thickness accuracy and uniform physical properties in the film width direction. Examples of stretching devices for flat-type simultaneous biaxial stretching method include screw-type tenter, pantograph-type tenter, and linear motor-driven clip-type tenter. From the viewpoint of the heat resistance and mechanical strength of the finally obtained semi-aromatic polyamide film, the stretching ratio is preferably 1.5 to 3.0 times in the longitudinal direction and 3.1 to 4.2 times in the width direction, and more preferably 2.2 to 2.5 times in the longitudinal direction and 3.6 to 3.9 times in the width direction. If the stretching ratio in the longitudinal direction exceeds 3.0 times, the obtained film has a lower transparency or progresses in crystallization, resulting in a lower stretchability. If the stretching ratio in the longitudinal direction is less than 1.5 times, the obtained film may have insufficient oriented crystallization and may have poor mechanical strength. Furthermore, in the case of sequential stretching, if the stretching ratio in the longitudinal direction is too high, it may be difficult to stretch the film in the width direction after that, making it difficult to stretch the film. Even if the film can be stretched, the obtained film is prone to stretching unevenness and may have a lower thickness precision. The stretching temperature is preferably equal to or higher than the glass transition temperature (Tg) of the semi-aromatic polyamide resin, and more preferably, higher than Tg and lower than (Tg+50°C). If the stretching temperature is lower than Tg, the film is easily broken and stable production cannot be performed, and conversely, if the stretching temperature exceeds (Tg+50°C), stretching spots may occur in the film. In addition, it is preferable to preheat the unstretched film prior to stretching. By preheating, it is possible to stretch the film in the stretching step while suppressing crystallization of the semi-aromatic polyamide resin. When, for example, polyamide 9T (glass transition temperature 130°C) is used as the semi-aromatic polyamide resin, the preheating temperature is preferably 105 to 160°C, more preferably 110 to 155°C, and the stretching temperature is preferably 120 to 170°C, more preferably 130 to 160°C, and even more preferably 135 to 155°C. By carrying out preheating and stretching within these temperature ranges, the stretching force during stretching can be reduced, and a stretched film with improved transparency can be obtained.
[0031] An example of the above step (c) will be described. After the semi-aromatic polyamide film is stretched as described above, it is preferable to perform a heat setting treatment while holding the film with the clips used in the stretching. By performing the heat setting treatment, the obtained film can have a reduced heat shrinkage rate without generating heat damage spots. The heat setting temperature is preferably 260 to 282° C., more preferably 263 to 280° C., and even more preferably 265 to 278° C. If the heat setting temperature is less than 260° C., the heat shrinkage of the resulting film will be high. If the heat setting temperature is more than 280° C., the tensile elongation at break of the resulting film will be reduced, and the film will be prone to poor appearance due to wrinkles caused by heat damage, and in some cases, breakage will occur during the heat setting process, making it difficult to obtain a biaxially stretched film. Examples of the heat setting method include known methods such as a method of blowing hot air, a method of irradiating infrared rays, a method of irradiating microwaves, etc. Among these, the method of blowing hot air is preferred because it can heat uniformly and accurately. After the heat setting treatment, the film is preferably subjected to a relaxation treatment of 1 to 12%, more preferably 3 to 10%, as necessary while still being held by the clips. By performing the relaxation treatment, the film can obtain sufficient dimensional stability.
[0032] Furthermore, an example of the above step (d) will be described. After stretching the semi-aromatic polyamide film, it is subjected to heat setting and relaxation treatment, cooled, and wound into a roll. The wound up stretched film roll of semi-aromatic polyamide resin is slit to a desired width.
[0033] <Easy adhesion layer> (copolymer polyester resin) The copolymerized polyester resin constituting the easy-adhesion layer of the easy-adhesion film of the present invention preferably contains 30 mol % or more, more preferably 40 mol % or more, and even more preferably 50 to 80 mol % of isophthalic acid as an acid component. If the content of isophthalic acid in the acid component of the copolymerized polyester resin is less than 30 mol %, the adhesiveness of the obtained easy-adhesion layer is reduced, and the solubility in organic solvents of the adhesive for forming the easy-adhesion layer also tends to be reduced.
[0034] Examples of the acid component other than isophthalic acid include terephthalic acid, naphthalenedicarboxylic acid, succinic acid, adipic acid, azelaic acid, sebacic acid, hexahydroterephthalic acid, phthalic acid, 4,4'-dicarboxybiphenyl, 5-sodium sulfoisophthalic acid, 5-hydroxy-isophthalic acid, fumaric acid, maleic acid, itaconic acid, mesaconic acid, citraconic acid, 1,3,4-benzenetricarboxylic acid, 1,2,4,5-benzenetetracarboxylic acid, oxalic acid, 1,3-cyclohexanedicarboxylic acid, 1,2-cyclohexanedicarboxylic acid, tetrahydrophthalic acid, and 2,5-norbornenedicarboxylic acid. Anhydrides of these may be used as monomer raw materials, or they may be used in combination. Among them, from the viewpoint of maintaining heat resistance, it is preferable to use terephthalic acid, naphthalenedicarboxylic acid, and hexahydroterephthalic acid as acid components other than isophthalic acid.
[0035] The glycol component of the copolymerized polyester resin preferably contains 30 mol% or more of glycol having a side chain, more preferably 40 mol% or more, and even more preferably 50 to 80 mol%. In the copolymerized polyester resin in which the content of glycol having a side chain in the glycol component is less than 30 mol%, the adhesiveness of the obtained easy-adhesion layer is reduced, and the solubility in organic solvents in the resin composition for forming the easy-adhesion layer tends to be reduced. On the other hand, if the content of glycol having a side chain exceeds 80 mol%, the adhesiveness of the obtained easy-adhesion layer tends to be reduced. Examples of glycols having a side chain include 1,2-propanediol, 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 2-methylpropanediol, 3-methyl-1,5-pentanediol, 2-ethyl-2-butylpropanediol, an ethylene oxide adduct of bisphenol A, a propylene oxide adduct of bisphenol A, trimethylolpropane, etc., and these may be used in combination. Among these, from the viewpoint of improving adhesiveness, 2,2-dimethyl-1,3-propanediol (neopentyl glycol) and an ethylene oxide adduct of bisphenol A are preferred as glycols having a side chain.
[0036] The glycol component of the copolymerized polyester resin preferably contains 1 to 20 mol %, more preferably 3 to 15 mol %, and even more preferably 4 to 10 mol % of a polyalkylene glycol having a carbon number of 2 to 4 in the repeating unit and a number average molecular weight of 200 or more. If the content of the polyalkylene glycol in the glycol component of the copolymerized polyester resin is less than 1 mol %, the glass transition temperature tends to be high, and the adhesiveness and moist heat resistance of the obtained easy-adhesion layer may be reduced. On the other hand, if the content of the polyalkylene glycol exceeds 20 mol %, the heat resistance of the obtained easy-adhesion layer may be poor. The polyalkylene glycol preferably has a number average molecular weight of 200 or more, more preferably 500 to 10000, and even more preferably 800 to 5000. By using a polyalkylene glycol having a number average molecular weight of 200 or more, the obtained easy-adhesion layer has improved resistance to moist heat. As the polyalkylene glycol having a repeating unit of 2 to 4 carbon atoms and a number average molecular weight of 200 or more, polyethylene glycol, polypropylene glycol, polytrimethylene glycol, and polytetramethylene glycol are preferred from the viewpoints of adhesiveness and resistance to moist heat.
[0037] Examples of glycol components other than those mentioned above include ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,4-cyclohexanedimethanol, and two or more of these may be used in combination.
[0038] Other components constituting the copolymerized polyester resin include hydroxycarboxylic acids such as lactic acid, glycolic acid, 2-hydroxybutyric acid, 3-hydroxybutyric acid, 4-hydroxybutyric acid, 2-hydroxyisobutyric acid, 2-hydroxy-2-methylbutyric acid, 2-hydroxyvaleric acid, 3-hydroxyvaleric acid, 4-hydroxyvaleric acid, 5-hydroxyvaleric acid, 6-hydroxycaproic acid, 10-hydroxystearic acid, 4-(β-hydroxy)ethoxybenzoic acid, and malic acid, aliphatic lactones such as β-propiolactone, β-butyrolactone, γ-butyrolactone, δ-valerolactone, and ε-caprolactone, and oxiranes, and these may be contained.
[0039] Furthermore, the copolymerized polyester resin may be copolymerized with a monocarboxylic acid or a monoalcohol, as necessary. Examples of the monocarboxylic acid include lauric acid, myristic acid, palmitic acid, stearic acid, oleic acid, linoleic acid, linolenic acid, benzoic acid, p-tert-butylbenzoic acid, cyclohexanoic acid, and 4-hydroxyphenylstearic acid, and examples of the monoalcohol include octyl alcohol, decyl alcohol, lauryl alcohol, myristyl alcohol, cetyl alcohol, stearyl alcohol, and 2-phenoxyethanol.
[0040] The above-mentioned monomers constituting the copolymerized polyester resin may be used in combination according to the desired properties. In addition, two or more types of copolymerized polyester resins may be mixed and used, and they may be phase-separated or uniformly mixed.
[0041] The copolymer polyester resin preferably has an acid value of 2 to 8 mgKOH / g, more preferably 3 to 7 mgKOH / g, and even more preferably 4 to 6 mgKOH / g. When the acid value of the copolymer polyester resin is within the above range, the resulting easy-adhesion layer has excellent adhesion to the metal plate and excellent heat resistance. When the copolymer polyester resin has an acid value of less than 2 mgKOH / g, the heat resistance is poor, and when the acid value exceeds 8 mgKOH / g, the resulting easy-adhesion layer may have poor adhesion to the metal plate.
[0042] Examples of a method for controlling the acid value of the copolymerized polyester resin include a method of producing a polyester resin having a high molecular weight and then adding a depolymerization agent, a method of adding an acid anhydride, etc. In the present invention, since both the acid value and the number average molecular weight described below of the copolymerized polyester resin can be controlled in a well-balanced manner, a method of producing a polyester resin having a high molecular weight and then adding a depolymerization agent to control the acid value and the number average molecular weight is preferred. As the depolymerization agent, isophthalic acid, adipic acid, sebacic acid, etc. are preferred, and as the acid anhydride, trimellitic anhydride, pyromellitic anhydride, etc. are preferred.
[0043] The copolymerized polyester resin preferably has a number average molecular weight of 10,000 to 50,000, more preferably 10,000 to 40,000, and even more preferably 10,000 to 30,000. If the number average molecular weight of the copolymerized polyester resin is less than 10,000, the peel strength of the resulting easy-adhesion layer may be somewhat poor. If the number average molecular weight of the copolymerized polyester resin is more than 50,000, the fluidity of the resulting solution of the resin composition for forming an easy-adhesion layer may decrease, making application difficult.
[0044] The copolymer polyester resin preferably has a glass transition temperature of -10 to 10°C, more preferably -8 to 9°C, and even more preferably -6 to 8°C. When the copolymer polyester resin has a glass transition temperature in the above range, the resulting easy-adhesion layer has excellent adhesion to the metal plate. When the copolymer polyester resin has a glass transition temperature of less than -10°C or more than 10°C, the resulting easy-adhesion layer has reduced adhesion to the metal plate.
[0045] (Resin composition for forming easy adhesive layer) In the present invention, the easy-adhesion layer can be formed using a resin composition containing a copolymerized polyester resin, an epoxy compound, and an imidazole compound.
[0046] The content of the epoxy compound in the resin composition is preferably 3 to 13 parts by mass, more preferably 3 to 12 parts by mass, and even more preferably 4 to 11 parts by mass, relative to 100 parts by mass of the copolymerized polyester resin. By containing the epoxy compound in the resin composition, the heat resistance of the obtained easy-adhesion layer is improved. If the content of the epoxy compound is less than 3 parts by mass, the heat resistance of the obtained easy-adhesion layer is reduced, while if the content exceeds 13 parts by mass, both the heat resistance and the adhesion of the obtained easy-adhesion layer are reduced.
[0047] The epoxy compound is not particularly limited as long as it is a compound having two or more epoxy groups per molecule. Suitable specific examples include polyethylene glycol, glycerin and its derivatives, polyhydric hydroxyl compounds such as sorbitol, in which a part of the hydroxyl groups is converted to a glycidyl group, such as sorbitol polyglycidyl ether, glycerol polyglycidyl ether, trimethylolpropane polyglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether, as well as novolac-type epoxy resins, bisphenol-type epoxy resins, trisphenolmethane-type epoxy resins, amino-group-containing epoxy resins, and copolymer-type epoxy resins. These may be used alone or in combination.
[0048] In addition, the resin composition preferably contains an imidazole compound as a curing accelerator, and the content is preferably 0.3 to 0.9 parts by mass, more preferably 0.3 to 0.8 parts by mass, and even more preferably 0.3 to 0.7 parts by mass, relative to 100 parts by mass of the copolymerized polyester resin. By containing the imidazole compound in the resin composition, the heat resistance of the obtained easy-adhesion layer is improved. If the content of the imidazole compound is less than 0.3 parts by mass, the heat resistance of the obtained easy-adhesion layer is reduced, while if the content exceeds 0.9 parts by mass, both the heat resistance and the adhesiveness of the obtained easy-adhesion layer are reduced.
[0049] Specific examples of the imidazole compound include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, 1-benzyl-2-phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidozolium trimellitate, 2,4-diamino-6-[ 2'-methylimidozolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidozolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct, 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, and the like. Among these, 2-undecylimidazole, 1-benzyl-2-phenylimidazole, and 1-cyanoethyl-2-undecylimidazole are preferred from the viewpoints of solubility in the adhesive for forming the easy-adhesion layer and stability during high-temperature processing. These may be used alone or in combination.
[0050] <Production of easily adhesive films> Next, a method for producing the easily adhesive film will be described. The easy-adhesion layer can be laminated on the base film by adding a step of providing an easy-adhesion layer between or before or after steps (a) to (d) in the method for producing a semi-aromatic polyamide film. Examples of the method for laminating the easy-adhesion layer include a method for applying a coating agent such as a solution of various solvents or an aqueous dispersion of the resin composition for forming an easy-adhesion layer, a method for heat-melting the resin composition for forming an easy-adhesion layer and extrusion coating, etc. Also included is a method for forming an easy-adhesion layer on the outermost layer when extruding an unstretched film of a semi-aromatic polyamide film in a multilayer manner. Regardless of the above means, any means may be used for providing an easy-adhesion layer on at least one side of the semi-aromatic polyamide film as long as the easy-adhesion layer is steadily formed on at least one side of the semi-aromatic polyamide film. Examples of the medium constituting the coating agent for forming the easy-adhesion layer include acetone, toluene, and methyl ethyl ketone. As a method for applying the coating agent for forming an easy-adhesion layer to a semi-aromatic polyamide film to form a coating film of the easy-adhesion layer, a known method can be used, such as gravure roll coating, reverse roll coating, wire bar coating, lip coating, air knife coating, curtain flow coating, spray coating, dip coating, brush coating, etc. By forming a coating film by the above method and then subjecting it to a drying heat treatment, the medium constituting the coating agent can be removed, and an easy-adhesion layer consisting of a dense coating film can be laminated on the semi-aromatic polyamide film.
[0051] <Laminate> The laminate of the present invention is obtained by laminating a metal plate on the adhesive layer surface of an adhesive film. The metal plate is not particularly limited, but examples thereof include copper, tin, aluminum, gold, nickel, and mixtures and compounds thereof. The laminate is prepared by placing a metal plate, such as rolled copper foil (18 μm), on the adhesive layer, and heating it from 30° C. to a predetermined temperature at a rate of 15° C. / min in a vacuum press at 1.07 kPa (8 Torr). 2 The resulting mixture can be obtained by applying and maintaining a pressure of 1000 MPa and then cooling to room temperature. In the present invention, the laminate is prepared into a rectangular shape of 150 mm x 10 mm, and the peel strength measured in a 180° peel test at 23°C x 50% RH and 200 mm / min is preferably 8.0 N / 15 mm or more. A laminate having a peel strength of less than 8.0 N / 15 mm has low adhesion to the metal plate, and the resulting flexible printed circuit board may have a risk of peeling off the metal plate during solder reflow.
[0052] <Application> The easily adhesive film of the present invention has excellent adhesion to metal plates while having heat resistance, and therefore can be used for transparent flexible printed circuit boards for optical components. Specifically, it can be used as a base film for flexible printed wiring in display materials and display devices for mobile devices, etc., such as various displays such as liquid crystal, organic EL, and LED screens. EXAMPLES
[0053] The present invention will be specifically described below with reference to examples, but the present invention is not limited to these. The semi-aromatic polyamide resin, copolymer polyester resin, and laminate were evaluated as follows. Unless otherwise specified, all measurements were performed in an environment of a temperature of 23° C. and a humidity of 50%.
[0054] (1) Melting point (Tm) and glass transition temperature (Tg) of semi-aromatic polyamide resin Using a DSC device (PerkinElmer DSC7), the semi-aromatic polyamide resin was heated from 20°C to 350°C at 10°C / min under a nitrogen atmosphere and held for 5 minutes (1st scan), then cooled from 350°C to 20°C at 100°C / min and held for 5 minutes. The glass transition temperature in the process of further heating from 20°C to 350°C at 10°C / min (2nd scan) was taken as Tg. Similarly, the peak top temperature of the crystal melting peak observed in the 2nd scan was taken as Tm.
[0055] (2) Tensile strength retention and tensile elongation retention of semi-aromatic polyamide film For the longitudinal direction of the semi-aromatic polyamide film, the tensile strength and tensile elongation (A) after heat treatment at 180℃ for 30 min and the tensile strength and tensile elongation (B) before heat treatment were measured in accordance with JIS K7127, and the retention rate was calculated based on the following formula. Retention rate (%)=(A / B)×100
[0056] (3) Composition of copolymer polyester resin Using an NMR device (JNM-ECZ400R / S1 manufactured by JEOL Ltd.), 1 The composition was determined from the peak intensity of each copolymer component by H-NMR measurement. A mixed solvent of deuterated trifluoroacetic acid and deuterated tetrachloroethane with a volume ratio of 1 / 11 was used as the measurement solvent.
[0057] (4) Number average molecular weight of copolymer polyester resin The number average molecular weight was determined using a GPC analyzer (Shimadzu Corporation, liquid delivery unit LC-10ADvp type and ultraviolet-visible spectrophotometer SPD-6AV type, detection wavelength: 254 nm, solvent: tetrahydrofuran, polystyrene equivalent).
[0058] (5) Glass transition temperature (Tg) of copolymer polyester resin The glass transition temperature (extrapolated glass transition onset temperature) was determined using a power compensation type differential scanning calorimeter (Diamond DSC manufactured by PerkinElmer) in accordance with JIS-K7121.
[0059] (6) Acid value of copolymer polyester resin 150 mg of copolymer polyester resin was weighed out and placed in a test tube, 5 mL of benzyl alcohol was added, the resin was dissolved by heating, and the resin was transferred to a Mayer flask containing 10 mL of chloroform. The test tube used was washed by heating with 5 mL of benzyl alcohol, and the washings were also transferred to the Mayer flask. The obtained copolymer polyester resin solution was titrated with 0.1 N KOH benzyl alcohol solution using phenol red as an indicator, and the acid value (mgKOH / g) of the copolymer polyester resin was calculated from the difference with the titration amount of the blank test.
[0060] (7) Haze of easily adhesive films The total light transmittance (Tt) and diffuse transmittance (Td) of the easily adhesive film were measured in accordance with JIS K7105 using a haze meter (NDH 2000) manufactured by Nippon Denshoku Industries Co., Ltd., and the haze was calculated based on the following formula to evaluate the transparency. The haze was measured as follows: Haze (%)=(Td / Tt)×100.
[0061] (8) Peel strength of laminate The laminate was cut into a rectangular shape of 150 mm x 10 mm, and using Shimadzu Corporation's "AUTOGRAPH AG-10kNIS", the chuck distance was set to 100 mm, the copper foil was attached to the upper chuck, and the copper foil was bent 180° at 23°C x 50% RH, 200 mm / min, and measurements were taken.
[0062] <Material> The following materials were used to form the base film. [Semi-aromatic polyamide resin (PA9T) pellets] 3289 parts by mass of terephthalic acid (TPA), 2533 parts by mass of 1,9-nonanediamine (NDA), 633 parts by mass of 2-methyl-1,8-octanediamine (MODA), 48.9 parts by mass of benzoic acid (BA), 6.5 parts by mass of sodium hypophosphite monohydrate (0.1% by mass relative to the total of the four polyamide raw materials) and 2200 parts by mass of distilled water were placed in a reactor and substituted with nitrogen. The molar ratio of these raw materials (TPA / BA / NDA / MODA) was 99 / 2 / 80 / 20. The contents of the reactor were stirred at 100°C for 30 minutes, and then the internal temperature was raised to 210°C over 2 hours. At this time, the internal pressure of the reactor was 2.12 MPa (22 kg / cm 2 The reaction was continued for 1 hour, after which the temperature was raised to 230°C and kept at 230°C for another 2 hours. The steam was gradually released and the pressure was reduced to 2.12MPa (22kg / cm 2 The reaction was carried out while maintaining the pressure at 0.98 MPa (10 kg / cm) for 30 minutes. 2) and reacted for another hour to obtain a prepolymer, which was dried at 100°C under reduced pressure for 12 hours and then crushed to a size of 2 mm or less. The pulverized prepolymer was then subjected to solid-phase polymerization for 10 hours at a temperature of 230°C and a pressure of 13.3 Pa (0.1 mmHg) to obtain a polymer. This was fed to a twin-screw extruder ("TEX44C" manufactured by Japan Steel Works, Ltd.), melt-kneaded and extruded at a cylinder temperature of 320°C, cooled, and cut to produce pellets of semi-aromatic polyamide resin (PA9T). The semi-aromatic polyamide resin (PA9T) had a melting point of 290°C and a glass transition temperature of 125°C.
[0063] [PA9T pellets containing silica particles (M1)] Semi-aromatic polyamide resin (PA9T) 98 parts by mass and 2 parts by mass of silica (manufactured by Fuji Silysia Chemical, Silohorbic 100, average particle size 2.7 μm) were melt-kneaded to produce semi-aromatic polyamide resin (PA9T) pellets (M1) containing silica particles.
[0064] [Semi-aromatic polyamide resin (PA10T) pellets] 489 parts by mass of terephthalic acid (TPA), 507 parts by mass of 1,10-decanediamine (DDA), 2.8 parts by mass of benzoic acid (BA), 1.0 part by mass of sodium hypophosphite monohydrate (0.1% by mass relative to the total of the three polyamide raw materials) and 1000 parts by mass of distilled water were placed in a reactor and purged with nitrogen. The molar ratio of these raw materials (TPA / BA / DDA) was 99 / 2 / 100. The contents of the reaction vessel were stirred at 28 revolutions per minute at 80° C. for 0.5 hours, and then heated to 230° C. Then, the contents were heated at 230° C. for 3 hours. After that, the contents were cooled and the reaction product was taken out. The reaction product was pulverized and then heated in a dryer under a nitrogen gas flow at 220°C for 5 hours to obtain a polymer by solid-state polymerization. The polymer was fed to a twin-screw extruder (TEX44C manufactured by Japan Steel Works, Ltd.), melt-kneaded and extruded under a cylinder temperature of 320°C, cooled, and cut to produce pellets of semi-aromatic polyamide (PA10T). The semi-aromatic polyamide (PA10T) had a melting point of 316°C and a glass transition temperature of 120°C.
[0065] [PA10T pellets containing silica particles (M2)] Semi-aromatic polyamide resin (PA10T) 98 parts by mass and silica (Fuji Silysia Chemical, Silohorbic 100, average particle size 2.7 μm) 2 parts by mass were melt-kneaded to produce semi-aromatic polyamide resin (PA10T) pellets (M2) containing silica particles.
[0066] [Hindered phenol-based heat stabilizer] Sumilizer GA-80: 3,9-bis[2-{3-(3-t-butyl-4-hydroxy-5-methylphenyl)propionyloxy}-1,1-dimethylethyl]-2,4,8,10-tetraoxaspiro[5.5]undecane (Sumitomo Chemical Co., Ltd., thermal decomposition temperature 392°C)
[0067] The following copolymer polyester resin was used as the copolymer polyester resin constituting the adhesive layer. [Copolymer polyester resin (A)] The raw materials were charged into an esterification reaction vessel so that the acid components were 50.0 mol % of terephthalic acid (TPA) and 49.2 mol % of isophthalic acid (IPA), the glycol components were 44.0 mol % of ethylene glycol (EG), 49.0 mol % of neopentyl glycol (NPG), 6.0 mol % of polytetramethylene glycol (PTMG) having a number average molecular weight of 1000, and 1.0 mol % of diethylene glycol (DEG), and the hindered phenol-based antioxidant was 0.25 mass % relative to the resulting copolymerized polyester resin, and esterification was carried out at 250°C for 5 hours under a pressure of 0.25 MPa with stirring to produce an esterified product. Thereafter, the mixture was transferred to a polycondensation tank, a polymerization catalyst was added, the pressure was gradually reduced to 1.3 hPa over 60 minutes, and a polycondensation reaction was carried out at 250° C. until a predetermined molecular weight was reached. Next, the polycondensation tank was filled with nitrogen to 0.1 MPa, trimellitic anhydride (TMA) was added so that the acid component was 0.8 mol %, and a depolymerization reaction was carried out at 250°C with stirring for 2 hours to obtain a copolymer polyester resin (A). The copolymer polyester resin (A) thus obtained had a number average molecular weight of 18,000, an acid value of 4 mgKOH / g, and a glass transition temperature of 5°C.
[0068] [Copolymer polyester resins (B) to (D)] Copolymer polyester resins (B) to (D) were obtained in the same manner as in the production of copolymer polyester resin (A), except that the composition of the copolymer polyester resin was changed as shown in Tables 1 and 2.
[0069] [Copolymer polyester resins (E) and (F)] Copolymer polyester resins (E) and (F) were obtained in the same manner as in the production of copolymer polyester resin (A), except that the composition of the copolymer polyester resin was changed as shown in Table 2 and the depolymerization reaction was not carried out.
[0070] Example 1 100 parts by mass of copolymer polyester resin (A) was dissolved in a mixed solvent of toluene / methyl ethyl ketone (8 / 2 (mass ratio)) to a solids concentration of 25% by mass, and 5 parts by mass of an epoxy compound (sorbitol polyglycidyl ether, manufactured by Nagase ChemteX, Denacol EX-614B) and 0.35 parts by mass of an imidazole compound (2-undecylimidazole, manufactured by Shikoku Kasei, C11Z) were added to prepare a solution (A) of a resin composition for forming an easy-adhesion layer. Semi-aromatic polyamide resin (PA9T), Sumilizer GA-80, and silica particle-containing PA9T pellets (M1) were mixed so that the amount of hindered phenol-based heat stabilizer and silica were 0.2 parts by mass per 100 parts by mass of semi-aromatic polyamide resin (PA9T). This mixture was put into an extruder and melted at 320°C, then extruded into a film from a T-die and cooled by pressing it against a cooling roll (ceramic coated with a thickness of 0.015 mm, actual surface temperature of 40°C) using an electrostatic application method to obtain a substantially unoriented unstretched film with a thickness of 450 μm. The unstretched film was then stretched 2.4 times in the longitudinal direction at 130°C using a roll-type longitudinal stretching machine, and the ends of the film were then continuously held by the clips of a flat-type stretching machine and stretched 3.8 times in the width direction at 126°C. The film was then heat-set at 278°C for 3 seconds with a relaxation rate of 4% in the width direction to obtain a biaxially stretched semi-aromatic polyamide film having a thickness of 50 μm. The solution (A) of the resin composition for forming an easy-adhesion layer was applied to one side of the obtained semi-aromatic polyamide film using a Mayer bar, and dried at 180°C for 30 seconds to obtain an easy-adhesion film having an easy-adhesion layer with a thickness of 12 μm. The haze of the easy-adhesion film was 3.9%. A rolled copper foil (JX Metals, 18 μm) was attached to the adhesive side of the obtained adhesive film, and the temperature was increased from 30° C. to 180° C. at a rate of 15° C. / min in a vacuum press at 1.07 kPa (8 Torr), and the pressure was increased to 30 kgf / cm. 2 While applying a pressure of 180° C., the laminate was heat-treated at 180° C. for 30 minutes to obtain a laminate.
[0071] Examples 2 to 10, Comparative Examples 1 to 4, 9 to 12 An easily adhesive film was obtained in the same manner as in Example 1, except that the type of copolymer polyester resin constituting the resin composition for forming an easily adhesive layer, the parts by mass of the epoxy compound and the imidazole compound, and the type of resin constituting the base film were changed as shown in Tables 1 and 2. In addition, a laminate was obtained by changing the temperature and time of copper foil lamination. In Comparative Examples 9 and 10, a PET film (Embret S50, manufactured by Unitika Ltd.) was used as the base film, and in Comparative Examples 11 and 12, a PEN film (Teonex Q-51, manufactured by Teijin Ltd.) was used.
[0072] Comparative Examples 5 to 6 An easily adhesive film and a laminate were obtained in the same manner as in Example 1, except that the composition of each unit constituting the urethane resin was hexanediol / diethyl carbonate / tolylene diisocyanate (25 / 30 / 45 (mol%)) and an aqueous dispersion having a solid content concentration of 20 mass% was used as a solution of the resin composition for forming an easily adhesive layer (Comparative Example 5). In addition, a laminate was obtained by changing the temperature for laminating the copper foil (Comparative Example 6).
[0073] Comparative Examples 7 to 8 A dimer acid polyamide was prepared containing 100 mol % dimer acid as the dicarboxylic acid component and 100 mol % ethylenediamine as the diamine component, with an acid value of 10.0 mgKOH / g, an amine value of 0.1 mgKOH / g and a softening point of 158°C. 75.0g of dimer acid polyamide, 37.5g of isopropanol, 37.5g of tetrahydrofuran, 7.2g of N,N-dimethylethanolamine, and 217.8g of distilled water were charged and heated and stirred at 120°C for 60 minutes. After that, it was cooled to about room temperature while stirring, and 100g of distilled water was added, and then filtered with a 300 mesh stainless steel filter. The obtained aqueous dispersion was reduced in pressure using an evaporator, and about 100g of the mixed medium of isopropanol, tetrahydrofuran, and distilled water was distilled off, and a milky white uniform aqueous dispersion of dimer acid polyamide resin was obtained. An easily adhesive film was obtained in the same manner as in Example 1, except that the obtained aqueous dispersion of dimer acid-based polyamide resin was used as a coating agent for the resin composition for forming an easily adhesive layer (Comparative Example 7). In addition, a laminate was obtained by changing the time for laminating the copper foil (Comparative Example 8).
[0074] Various performance evaluations were carried out using the laminates obtained in Examples 1 to 10 and Comparative Examples 1 to 12. The film compositions and physical properties are shown in Tables 1 and 2.
[0075] [Table 1]
[0076] [Table 2]
[0077] The easily adhesive films of Examples 1 to 10 had the configuration specified by the present invention, and therefore had heat resistance and high adhesiveness to the metal plate. In Comparative Examples 1 to 8, the heat resistance was good, but the adhesion to the metal plate was low, and in Comparative Examples 9 to 12, the adhesion to the metal plate was high, but the heat resistance was poor.
Claims
1. An easy-adhesion film having an easy-adhesion layer on at least one surface of a base film, The base film is made of a semi-aromatic polyamide resin, The easy-adhesion layer contains a copolymer polyester resin, An easily adhesive film, characterized in that in a laminate in which a metal plate is laminated on the surface of an easily adhesive layer, the peel strength between the base film and the metal plate is 8.0 N / 15 mm or more.
2. The easy-adhesion layer is formed using a resin composition containing 100 parts by mass of a copolymerized polyester resin, 3 to 13 parts by mass of an epoxy compound, and 0.3 to 0.9 parts by mass of an imidazole compound. The easy-adhesion film according to claim 1.
3. The copolymer polyester resin is The acid component contains 30 mol % or more of isophthalic acid, The easily adhesive film according to claim 1 or 2, characterized in that the glycol component contains 30 mol% or more of a glycol having a side chain and 1 to 20 mol% of a polyalkylene glycol having a repeating unit with 2 to 4 carbon atoms and a number average molecular weight of 200 or more.
4. 3. The easily adhesive film according to claim 1, wherein the copolymer polyester resin has an acid value of 2 to 8 mgKOH / g and a glass transition temperature of -10 to 10°C.
5. 3. The easily adhesive film according to claim 1, wherein the base film retains a tensile strength of 80% or more and a tensile elongation of 80% or more after heat treatment at 180° C. for 30 minutes.
6. A laminate comprising a metal plate laminated on the adhesive layer surface of the adhesive film according to claim 1.
7. 7. The laminate according to claim 6, wherein the peel strength between the substrate film and the metal plate is 8.0 N / 15 mm or more.
8. 8. The laminate according to claim 6 or 7, wherein the metal sheet is a copper foil.
9. An optical component using the laminate according to claim 6 or 7.
Citation Information
Patent Citations
Easy adhesive film
JP2021047295A
Laminated body
WO2019054426A1
